MODELS AND METHODS OF INFORMATION PROTECTION IN CYBERPHYSICAL SYSTEMS. - Pogasii , Serhii (Ukrainian Scientific Journal of Information Security, 2022)
The article presents a new approach to ensuring the security of information resources in cyber-physical systems. Today, such systems, as a rule, belong to objects of critical infrastructure. These systems are formed as a result of the integration of various elements of mobile communication technologies, classic computer networks and systems, as well as Internet of Things and Internet technologies. The work proposes consideration of the formation of the security system based on multi-contours, which allows considering two contours of the security system - internal (physical infrastructure of cyberphysical systems) and external (infrastructure of the control system based on cloud technologies). With the help of the developed classifier of threats to critical infrastructure objects, the formation of a classifier of attackers is ensured, in which its financial and computing capabilities are determined, which allows, based on the analysis of threats, to determine in a timely manner the degree of capabilities of attackers, as well as their intentions, and to form preventive protection measures. The use of the proposed protection models based on the Lotka-Volterra model allows considering the trends in the development of modern technologies, as well as the vector of cyber threats directed at critical infrastructure objects, which include modern cyberphysical systems. To ensure the security of information transmission through open channels of the cyber-physical systems network, information protection methods are proposed based on post-quantum algorithms – McEliece crypto-code constructions on LDPC codes, which allows to "close" the data transmission channels of the cyberphysical systems infrastructure.